A Case Study: Designing a Restaurant Marketing Strategy - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
In this report, they have established a marketing strategy for a Surabaya restaurant. A café-restaurant, serving mid-low customers, is the restaurant. For this restaurant, a clear marketing strategy has never been the main problem. Promotions implemented to the degree that they are not based on a campaign are not targeted and have no impact on revenue. The use of business intelligence from Power Market Intelligence (Power BI) will be a way of predicting customer consumption patterns for restaurants. However, with Market Basket Analysis they also model the demand trend. Captured service consumer consumption patterns used for the implementation of a 4P (product, location, price or promotion) framework for the proper marketing strategy. Some of the restaurant menus have been found to have a unique relationship and can be used for the promotion of profits. Certain findings cover child and office employees in the business category. This data is enabled with the Power BI dashboard, which will allow the review of improvements in revenue by the restaurant’s managers based on events and activities.